Zeolitic imidazolate framework (ZIF)-derived, hollow-core, nitrogen-doped carbon nanostructures for oxygen-reduction reactions in PEFCs - Palaniselvam, Thangavelu; Biswal, Bishnu P.; Banerjee, Rahul; Kurungot, Sreekumar (Chemistry-A European Journal, 2013)
The facile synthesis of a porous carbon material that is doped with iron-coordinated nitrogen active sites (FeNC-70) is demonstrated by following an inexpensive synthetic pathway with a zeolitic imidazolate framework (ZIF-70) as a template. To emphasize the possibility of tuning the porosity and surface area of the resulting carbon materials based on the structure of the parent ZIF, two other ZIFs, that is, ZIF-68 and ZIF-69, are also synthesized. The resulting active carbon material that is derived from ZIF-70, that is, FeNC-70, exhibits the highest BET surface area of 262m2g-1 compared to the active carbon materials that are derived from ZIF-68 and ZIF-69. The HR-TEM images of FeNC-70 show that the carbon particles have a bimodal structure that is composed of a spherical macroscopic pore (about 200nm) and a mesoporous shell. X-ray photoelectron spectroscopy (XPS) reveals the presence of Fe-N-C moieties, which are the primary active sites for the oxygen-reduction reaction (ORR). Quantitative estimation by using EDAX analysis reveals a nitrogen content of 14.5wt.%, along with trace amounts of iron (0.1wt.%), in the active FeNC-70 catalyst. This active porous carbon material, which is enriched with Fe-N-C moieties, reduces the oxygen molecule with an onset potential at 0.80V versus NHE through a pathway that involves 3.3-3.8e- under acidic conditions, which is much closer to the favored 4e- pathway for the ORR. The onset potential of FeNC-70 is significantly higher than those of its counterparts (FeNC-68 and FeNC-69) and of other reported systems. The FeNC-based systems also exhibit much-higher tolerance towards MeOH oxidation and electrochemical stability during an accelerated durability test (ADT). Electrochemical analysis and structural characterizations predict that the active sites for the ORR are most likely to be the insitu generated NFeN2+2/C moieties, which are distributed along the carbon framework.
Keywords: Doping; Electrochemistry; metal-organic frameworks; Nanostructures; oxygen-reduction reaction

ZIF-8@PBI-Bul composite membranes: elegant effects of PBI structural variations on gas permeation performance - Bhaskar, Anand; Banerjee, Rahul; Kharul, Ulhas K. (Journal of Materials Chemistry A, 2014)
The composites of metal organic frameworks (MOFs) and polymers look promising as membrane materials for gas separation, provided benefits of both the components can be shown successfully. This work shows that the structural architecture of polybenzimidazole (PBI) is highly advantageous in offering attractive gas permeation properties of its composites with MOFs. PBI-Bul and its N-substituted (methyl and 4-tert-butylbenzyl) derivatives were blended with ZIF-8. In general, homogeneous blend formation of ZIF-8 was achieved with all three polymers, as supported by SEM. Wide angle X-ray diffraction, mechanical property analysis and density measurements of the composite membranes were performed in order to understand the effects of physical blending of MOFs and polymers. Gas permeability analysis of the composite membranes revealed that the properties of MOFs as well as those of polymers arising from their structural architecture are responsible for governing the permeability and selectivity of the resulting composites.

ZIF-8@DBzPBI-BuI composite membranes for olefin/paraffin separation - Kunjattu, Shebeeb H.; Ashok, Varsha; Bhaskar, Anand; Pandare, Kiran; Banerjee, Rahul; Kharul, Ulhas K. (Journal of Membrane Science, 2018)
ZIF-8 is a member of Zeolitic Imidazole Framework family having high internal surface area, the high thermo-chemical stability and ease of synthesis gained immense attention for its highly selective sieving ability. Transforming it into a membrane form and practical utility remains a challenge. Any success towards this direction would radically reduce the cost of propylene/propane separation. Present study reports use of substituted polybenzimidazole (DBzPBI-BuI) for fabrication of flexible, thus scalable composite membranes with ZIF-8 (ZIF8@DBzPBI-BuI) possessing host-guest compatibility. The membrane with 30% ZIF-8 loading showed promising propylene-propane separation (ideal selectivity of 32.7), coupled with propylene permeability of 12.13 Barrer. Analysis of sorption shed light on the high contribution of diffusivity on governing permeation properties of the composite membranes. The mixed gas analysis offered highly encouraging results in comparison to known composite membranes of different polymers with ZIF-8. Placement of present data on `upper-bound' showed a rapid enhancement in selectivity by the addition of ZIF-8 in the polymer matrix, which seems to be a result of the elimination of inter-phase defects. It was made possible due to the functionality of host polymer.
Keywords: Gas permeation; Olefin/paraffin separation; Polybenzimidazole (PBI); ZIF-8

Zinc ion interactions in a two-dimensional covalent organic framework based aqueous zinc ion battery - Mohammed, Abdul Khayum; Ghosh, Meena; Vijayakumar, Vidyanand; Halder, Arjun; Nurhuda, Maryam; Kumar, Sushil; Addicoat, Matthew; Kurungot, Sreekumar; Banerjee, Rahul (Chemical Science, 2019)
<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">The two-dimensional structural features of covalent organic frameworks (COFs) can promote the electrochemical storage of cations like H<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">, Li<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">, and Na<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> through both faradaic and non-faradaic processes. However, the electrochemical storage of cations like Zn<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">2+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> ion is still unexplored although it bears a promising divalent charge. Herein, for the first time, we have utilized hydroquinone linked β-ketoenamine COF acting as a Zn<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">2+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> anchor in an aqueous rechargeable zinc ion battery. The charge-storage mechanism comprises of an efficient reversible interlayer interaction of Zn<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">2+<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> ions with the functional moieties in the adjacent layers of COF (−182.0 kcal mol<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">−1<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">). Notably, due to the well-defined nanopores and structural organization, a constructed full cell, displays a discharge capacity as high as 276 mA h g<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">−1<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;"> at a current rate of 125 mA g<small style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">−1<span style="color: rgba(0, 0, 0, 0.79); font-family: source-sans-pro, museo_sans300, Arial, sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 300; letter-spacing: -0.32px;">.